2021
DOI: 10.3390/rs13122386
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Forest Fires in Southeastern Australia Using SAR Data

Abstract: Prescribed burning is a common strategy for minimizing forest fire risk. Fire is introduced under specific environmental conditions, with explicit duration, intensity, and rate of spread. Such conditions deviate from those encountered during the fire season. Prescribed burns mostly affect surface fuels and understory vegetation, an outcome markedly different when compared to wildfires. Data on prescribed burning are crucial for evaluating whether land management targets have been reached. This research develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Wildfires are a common natural occurrence in many environments and constitute a vital component for their management. However, fires of high severity that cause devasting impacts over large areas have recently been documented, notably in the United States of America, the Mediterranean region, Australia, and Pakistan [1][2][3][4][5], bringing into question the effectiveness of current management practices, as these severe wildfires lead to an undesirable alteration and degradation of the landscape [6]. Many variables influence the severity of a fire, including elevation, slope and aspect [7], weather and climatic conditions [8], the structural characteristics of the forest, such as the density of trees and their diameter [9], and the history of fires in the area [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wildfires are a common natural occurrence in many environments and constitute a vital component for their management. However, fires of high severity that cause devasting impacts over large areas have recently been documented, notably in the United States of America, the Mediterranean region, Australia, and Pakistan [1][2][3][4][5], bringing into question the effectiveness of current management practices, as these severe wildfires lead to an undesirable alteration and degradation of the landscape [6]. Many variables influence the severity of a fire, including elevation, slope and aspect [7], weather and climatic conditions [8], the structural characteristics of the forest, such as the density of trees and their diameter [9], and the history of fires in the area [10].…”
Section: Introductionmentioning
confidence: 99%
“…The mapping of burned areas using SAR images relies on changes in the backscattering of the radar signal, which varies depending of the severity of the fire [3,22]. C-band SAR data have previously been used to investigate the extent of burned areas subsequent to fires in Australia and California, and it was found that the vertical horizontal (VH) polarization responded well to the occurrence of fires [3,22]. Other studies have also found that SAR imagery allowed for the detection and extent of burn scars in the landscape [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The district has the world's second largest salt mine (Khewra salt mine), which covers an area of 2.268 million acres [54]. People of the area have diverse modes of lifestyles, beliefs, and traditions [56]. Some typical landscapes are shown in Figure 2.…”
Section: Study Areamentioning
confidence: 99%
“…Appropriate classification techniques are fundamentally essential to generate reliable forest maps [27]. The classification methods were divided into supervised image classification, unsupervised image classification, and manual and calibration categories.…”
Section: Articles Published In the Pre-2010 Periodmentioning
confidence: 99%